A revision of the genus Beesia (Ranunculaceae) as informed through integrative taxonomy, with description of a new species from Sichuan (China) - Erst, Andrey S.; Mitrenina, Elizaveta Yu.; Krivenko, Denis A.; Erst, Tatyana V.; Cheldysheva, Yulia V.; Gorbenko, Igor V.; Borosova, Renata; Lian, Lian; Ling, Yuan-Yuan; Peng, Huan-Wen; Zhang, Jun; Baasanmunkh, Shukherdorj; et al. (Frontiers in Plant Science, 2026)
IntroductionTaxonomic diversity at different levels of organization is determined by different levels of biological diversity, including morphological, phylogenetic (genetic or/and genomic), and cytogenetic differences. However, focused studies utilizing a robust combination of such data are still in their infancy in plant systematics.MethodsHere, we integrate multiple forms of data to better understand species delimitation and taxonomy within the eastern Asiatic genus Beesia (Ranunculaceae), traditionally thought to include two species. Specifically, 26 morphological characters were measured, plastome regions were compared to reconstruct evolutionary relationships, and novel karyotype data were generated.ResultsMorphological analyses parsed three species of Beesia, with little overlap expressed for most measured characters. Phylogenetic data reconstructed these species into monophyletic groups, and cytogenetic data uncovered distinct karyotypes between taxa. This integrative taxonomic approach enabled delimitation of a new cryptic species from Sichuan (China): Beesia yangii Erst & K.L. Xiang. In addition, suitable lectotypes for Cimicifuga calthifolia Maxim. ex Oliv., Beesia cordata Balf.f. & W.W.Sm., and Beesia elongata Hand.-Mazz.DiscussionOur study helps demonstrate how broader application of integrative approaches in systematic biology may both better inform recognition of previously undiscovered taxonomic diversity and better inform outlines for conservation of biodiversity. The newly uncovered species, B. yangii, is known from very few localities and is already of critical conservation concern.